2021
DOI: 10.1101/2021.01.12.21249661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GIS-Based Analysis Framework for identifying COVID-19 Incidence and Fatality Determinants at National Level Case study: Africa

Abstract: BackgroundCOVID-19 pandemic is an extraordinary threat with significant implications in all aspects of human life, therefore, it represents the most immediate challenges for all countries all over the world.ObjectivesThis study is intended to develop a GIS-based analysis model to explore, quantify and model the relationships between COVID-19 morbidity and mortality and their potential predictor variables.MethodFor this purpose, a model was developed to estimate COVID-19 incidence and fatality rates in Africa u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, the analysis showed (only in Model 1) that the increase in the share of energy taxes in total taxes negatively impacts the health index, which may raise some additional questions as to why, since environmental taxes in relation to GDP have a positive effect in general. This could be surprising since, for example, a study by Hassan et al (2021) presenting the impact of these taxes on physical investment, human capital and environmental innovation found that energy taxes negatively impact polluting emissions. In turn, this should translate into health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the analysis showed (only in Model 1) that the increase in the share of energy taxes in total taxes negatively impacts the health index, which may raise some additional questions as to why, since environmental taxes in relation to GDP have a positive effect in general. This could be surprising since, for example, a study by Hassan et al (2021) presenting the impact of these taxes on physical investment, human capital and environmental innovation found that energy taxes negatively impact polluting emissions. In turn, this should translate into health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…JHUM, 2020). Even though mapping of risk or correlations is advancing (e.g., Al‐Kindi et al., 2020; Hassaan et al., 2021) the potential of GIS as a helping tool to understand COVID‐19 is far from being fully utilized (Ahasan & Hossain, 2021). We here integrate GIS and statistics to find both a (visualized) pattern and statistical correlations between COVID‐19 and environmental factors.…”
Section: Methodsmentioning
confidence: 99%
“…Early forecasting of the potential outbreaks is key in making effective infection prevention and control strategies [6]. Combating and proper management of COVID-19 spread, therefore requires an understanding of the key determinants of its morbidity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mapping disease outbreaks can also assist in understanding their key determinants [7]. Statistical analysis of spatial patterns is more effective as it involves assessing statistical significance of clustering or dispersion and modelling spatial relationships.…”
Section: Introductionmentioning
confidence: 99%